416 MRI Findings in Preterm Infants Associated with Strabismus - Jacob I. Strelnikov; Rachel Lean; Christopher D. Smyser; Cynthia Rogers; Mae Gordon; John R. Pruett; Susan Culican; Savannah Seupaul; Alisha Dhallan; Margaret Reynolds (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Prematurity and perinatal brain injury are known risk factors for strabismus. In this study, we sought to understand the link between neonatal neuroimaging measures in very preterm infants and the emergence of strabismus later in life. Study findings may inform if neonatal brain MRI could serve as a prognostic tool for this visual disorder. METHODS/STUDY POPULATION: This study draws from a longitudinal cohort of very preterm infants (VPT, < 30 weeks gestation, range 23 – 29 weeks) who underwent an MRI scan at 36 to 43 weeks postmenstrual age (PMA). Anatomic and diffusion MRI data were collected for each child . A subset of thirty-three patients in this cohort had records of an eye exam, which were reviewed for a history of strabismus. Patients with MRI scans demonstrating cystic periventricular leukomalacia or grade III/IV intraventricular hemorrhage were classified as having brain injury. Clinical variables with a known association to strabismus or diffusion metrics were included in a multivariable logistic regression model. Diffusion tractography metrics were screened for association with strabismus on univariable analysis prior to inclusion in the regression model. RESULTS/ANTICIPATED RESULTS: A total of 17/33 (51.5%) patients developed strabismus. A logistic regression model including gestational age, PMA at MRI, retinopathy of prematurity (ROP) stage, brain injury, and fractional anisotropy of the right optic radiation was significant at the .001 level according to the chi-square statistic. The model predicted 88% of responses correctly. Each decrease of 0.01 in the fractional anisotropy of the right optic radiation increased the odds of strabismus by a factor of 1.5 (95% CI 1.03 – 2.06; p = .03). Patients with brain injury had 15.8 times higher odds of strabismus (95% CI 1.1 – 216.5; p = .04). Gestational age (OR 1.7; 95% CI 0.9 – 3.3; p = .1) and stage of ROP (OR 0.6; 95% CI 0.2 – 2.0; p = .4) were not significant predictors of strabismus in the multivariable model. DISCUSSION/SIGNIFICANCE: Our findings suggest that strabismus in VPT patients may be related to specific changes in brain structure in the neonatal period. The identified association between neonatal optic radiation microstructure and strabismus supports the possibility of using brain MRI in very preterm infants to prognosticate visual and ocular morbidity.